Humor functions and flouting of conversatiomal maxims: A case study of humor in Indonesian academic lectures - Alawiyyah Alawiyyah; Wawan Gunawan; Ruswan Dallyono (Universitas Pendidikan Indonesia (UPI), 2020)
This case study explored the unlikely phenomenon of the use of humor in academic lectures. The previous studies in this area have shown that, though traditionally unlikely, humor is commonly used as a linguistic strategy in academic discourse. Therefore, this case study aims to contribute to the literature of Indonesian academic discourse by examining the creation and functions of humor in Indonesian academic lectures. Through the descriptive qualitative method, this study analyzed five classroom lectures of English Literature major in Universitas Pendidikan Indonesia. After the lectures were transcribed according to Jefferson’s (2004) transcription convention, the question of the creation of humor was answered based on Grice’s (1975) conversational maxim theory. This analysis discovered that there was a slight inclination to create humor by flouting the Maxim of Quality in the data, which implies that the lecturers tend to rely on untruthfulness to create jokes. Afterward, the function is analyzed based on Nesi’s (2012) theory of functions of humor in academic contexts, and it was found that the lecturers mostly used humor to build rapport with the students.Keywords: Academic context, Conversational maxims, Cooperative principles, Humor, Functions of humor, Pragmatics